A VIDEO GUIDELINE ON GIVING INFORMATION: A SOLUTION FOR THE RECEPTIONISTS’ LACK OF ENGLISH COMMUNICATION SKILLS AT THE ALANA HOTEL SURABAYA - Agnes Kiong; Jusuf I Ibrahim (Institute of Research and Community Outreach - Petra Christian University, 2014)
During my internship at an apartment equivalent to a three-star hotel, I found that the receptionists, who were mostly graduates from vocational high schools in hospitality major, had difficulty in giving information to foreign guests in English appropriately. As a result, the receptionists made the guests dissatisfied and unable to give a satisfactory service. From this communication problem, I thought that a video guideline on giving information in English would be the best solution for the problem. A guideline in a video will help the receptionists easier to learn about the guideline because they can just easily watch the role plays and listen the conversation. This video guideline which contains the steps and procedures for asking and giving information about check ins, hotel facilities, and check outs in English will help the receptionists to handle foreign guests appropriately and help hotels to maintain their customers by giving satisfactory services to the guests.